Rekonstruksi Tiga Sesar Utama pada Daerah Sambirejo, Kabupaten Gunung Kidul, Daerah Istimewa Yogyakarta - Ahmad, Ghani Abdillah; Erlandi, Muhammad; Rizqi, Al Hussein Flowers (ReTII, 2024)
This research area is one that has a very complex geological structure, so it is very interesting to study. Based on regional physiography and stratigraphy, it is included in the physiography of the Southern Mountains Zone which is composed of the Semilir Formation and Oyo Formation tuff lithology. The research method in the form of taking geological structures is carried out by observing data such as measuring fracture data, faults and other geological structure characteristic data in the Sambirejo Area, Gunung Kidul. Studio analysis in the form of processing fracture and fault data using stereonet and dips software. Based on the results of field observations, the geological structure in the research area is controlled by the presence of fractures and faults. The fractures found in the field are: shear fractures, and gash fractures. The faults found in the Sambirejo Area are minor faults. Determination of the type and kinematics of the main fault is carried out based on the appearance of minor faults in the field. The results of the fault kinematic reconstruction obtained the presence of main fault control in the form of Right Slip Fault or horizontal fault movement to the right with a relative west-east direction, Left Slip Fault or horizontal fault movement to the left with a relative northwest-southeast direction, Reverse Left Slip Fault or horizontal fault movement to the left rising with a relative northeast-southwest direction.